Berberine alleviates chronic pain-induced anxiety-like behaviors by inhibiting the activation of VLT-projecting cACC (Cg2) neurons - Min He; Ye-Xiang Chen; Pei-Pei Feng; Jie Chen; Chi Xu; Shu-Ting Zhou; Bo-Yu Liu; Xiao-Fen He; Xiao-Mei Shao; Jian-Qiao Fang; Zui Shen; Jing-Gen Liu (Communications Biology)
Abstract Chronic pain is often accompanied by anxiety, and gradually increasing anxiety makes the pain itself more protracted. Berberine has been found to be able to cross the blood–brain barrier to treat psychiatric disorders, but its neurocirculatory mechanisms remain unclear. Here, we found that neurons in cingulate area 2 (Cg2) of the caudal anterior cingulate cortex (cACC), but not in Cg1 of the cACC, projected to the ventral lateral thalamus (VLT). Next, we induced chronic inflammatory pain by plantar injection of complete Freund’s adjuvant (CFA) and observed stable anxiety-like behaviors until two weeks postinjection. We specifically activated VLT-projecting cACC (Cg2) neurons in one-week-old CFA-induced mice without anxiety-like behaviors and in normal control mice to induce anxiety-like behaviors. We inhibited the activation of VLT-projecting cACC (Cg2) neurons in two-week-old CFA-treated mice with anxiety-like behaviors and observed that their anxiety-like behaviors were alleviated. On this basis, we further screened the effective dose of berberine for anxiolysis in two-week-old CFA-treated mice. We observed that the effective dose of berberine obtained above decreased the activity of VLT-projecting cACC (Cg2) neurons. The activation of VLT-projecting cACC (Cg2) neurons abrogated the anxiolytic effect of berberine in two-week-old CFA-treated mice.